Dampak Penggunaan Smartphone Terhadap Karakter Peserta Didik - Kelvin Fesly; Nazwa Fadilatun Sulis (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The aim of this research is to determine the impact of smartphone use in the school environment by Cimuncang State Elementary School students. The use of smartphones has penetrated all levels of society. Monitoring smartphone use by parents and teachers is important to encourage student development. Smartphone misuse can influence student behavior and personality. The method used in this research is qualitative. The data collection technique in this research is based on field observations and interviews with informants to obtain the necessary data. Survey results show that students use smartphones because they need to notify their parents when they come home from school, and sometimes they use smartphones at school to study learning material that is not in school books and then can play online game applications, watch videos received from friends, and take photos with friends. When students become addicted to smartphones, their personality and social behavior change, there are students who become individualistic, rarely interact with the outside world and their classmates, and fall asleep when study time starts, and laze around when the teacher gives assignments, then when break time arrives. students use and follow everything in smartphone videos so that it has an impact on behavior or character at school.